Language Learning Styles And Strategies Of Preservice Teachers Its Relationship To Their Learning Engagement During Covid-19 Pandemic (Journal of Namibian Studies : History Politics Culture, 2023)
Language teaching is a difficult task for teachers since it requires the application of proper strategies and methods to achieve efficient language learning. This study aims to evaluate how university pre-service teachers learned languages and how they engaged in language learning during the COVID-19 Pandemic. 100 University pre-service teachers for the second semester of the academic year 2020–2021 took part in this research. To comprehend the factors, the researcher performed analysis. Descriptive statistics were used to analyze the profile variables and interpret the acquired data, including frequency counts, student data, mean, and standard deviation. The respondents' significant mean scores when categorized according to their profile were examined using sample T-test and ANOVA. Through Google Forms, significant data were gathered and recorded. With a categorical mean of 4.32 (sd=0.05) and a descriptive interpretation of Very High, the findings indicate that Teacher-Modelling Items are the preferred learning method for the majority of students. With a categorical mean of 4.09 (sd=.58) and an emotional learning style, learners' learning engagement throughout the COVID-19 Pandemic can be demonstrated. In summary, instructors' use of examples helps students learn knowledge quickly. The learning of university-trained pre-service teachers is governed by emotion. It is advised that instructional tactics match up with students' learning plans. Additionally, in order to effectively meet the needs of the students, teachers must devise a variety of activities and appropriate teaching materials.